Family Names and Family Settlements in the Village of Tskhiri, Gali Region - Kekua, Sopio (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
The village of Tskhiri is located within the occupied territory of Abkhazia in the Gali region approximately 12 kilometers from Gali. Extending across a significant area on both sides of the Eristsali River, Tskhiri was historically divided into three villages in 1930. One village became part of the first village council of Gali, the second joined the Recho-Tshiri council, and the third integrated with the Tskhiro-Gali village committee, assuming the name «Kvemo Tskhiri.» Eventually, Tskhiri established its village council with Tskhiri village serving as its center. Presently, Tskhiri falls under the Tkvarcheli region, an artificial administrative division that encompasses portions of the Gali and Ochamchire villages. However, it adopted the name «Tshir» upon becoming part of this region. The village is located 70 kilometers away from the contemporary regional center. The local population categorizes Tskhiri into three districts: Tshiti, Jhin Tskhiti (Upper Tskhiri), and Etseri. These districts are further subdivided into ancestral neighborhoods, with each district housing closely related families. The ancestral neighborhoods primarily consist of one family, resulting in their relatively small size. According to local classifications, there are currently five ancestral neighborhoods: Sazukhbaio (derived from Zukhbaia), Sakamkio (derived from Kamkia), Sanakofio (derived from Nakofia), Sarodonaio (derived from Rodonaia), and Satsatavo (derived from Tsatava). While only one family remains from the Zukhbaia, Kamkia, and Tsatava communities, their ancestral neighborhoods, namely Sazukhbaio, Sakamkio, and Satsato, have endured. The data presented in this article was collected in 2022 in the village of Tskhiri. The objective of this research is to examine the changes in family settlements within Tskhiri over the past two decades. Before the war, approximately 30 family names were recorded in the village, which decreased to 25 following the conflict. The current residents have identified the following family names in the village: Alsandia, Alphenidze, Aronia, Bakarandze, Buava, Gogilandze, Gogokhia, Esaia, Zukhbaia, Kamkia, Kortava, Krementsovi, Laishvili, Matua, Nakopia, Rodonaia, Uzarashvili, Shafanski, Chekheria, Tsaguria, Tsatava, Tsikolia, Tsimitia, Cholaria, and Khiklandze. The family names that emerged in the village after the war include Krementsovi, Tsaguria, and Cholaria. Despite recent developments, there has not been an ethnic transformation within the village. Georgian families have historically populated the area, a characteristic that remains true to this day. However, the population has significantly declined, with approximately 100 households in the past reducing to around 40 presently. While there is one family of Polish origin, they also speak Georgian like the rest of the residents.